2021
DOI: 10.1097/rli.0000000000000831
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional H-Scan Ultrasound Imaging of Early Breast Cancer Response to Neoadjuvant Therapy in a Murine Model

Abstract: ObjectivesThree-dimensional (3D) H-scan is a new ultrasound (US) technique that images the relative size of acoustic scatterers. The goal of this research was to evaluate use of 3D H-scan US imaging for monitoring early breast cancer response to neoadjuvant therapy using a preclinical murine model of breast cancer.Materials and MethodsPreclinical studies were conducted using luciferase-positive breast cancer–bearing mice (n = 40). Anesthetized animals underwent US imaging at baseline before administration with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…At termination (day 10), results from our study revealed that the averaged intensity of H‐scan US image was linearly proportional to nuclear size, proliferation, and apoptotic activity, which are all intimately related histological features. This observation supports previous studies that showed a linear relationship between H‐scan US image intensity and tumor cell nuclear size measurements from registered histology images 22,26,27 . In addition to mean‐value H‐scan US measurements of the segmented tumor volumes, a textural feature referred to as homogeneity was examined.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…At termination (day 10), results from our study revealed that the averaged intensity of H‐scan US image was linearly proportional to nuclear size, proliferation, and apoptotic activity, which are all intimately related histological features. This observation supports previous studies that showed a linear relationship between H‐scan US image intensity and tumor cell nuclear size measurements from registered histology images 22,26,27 . In addition to mean‐value H‐scan US measurements of the segmented tumor volumes, a textural feature referred to as homogeneity was examined.…”
Section: Discussionsupporting
confidence: 87%
“…This observation supports previous studies that showed a linear relationship between H-scan US image intensity and tumor cell nuclear size measurements from registered histology images. 22,26,27 In addition to mean-value H-scan US measurements of the segmented tumor volumes, a textural feature referred to as homogeneity was examined. Recall this image feature is helpful for quantifying the spatial relationship between local US scattering within the tumor space.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Output from the matched filters is then weighted and used to colorize an image to provide local discrimination between various-sized ultrasound scatterers. Several recent reports have detailed the use of in vivo H-scan ultrasound imaging for purposes ranging from the early detection of liver steatosis [18] , [19] , [20] to monitoring cancer response to treatment [21] , [22] , [23] . We envision that the H-scan ultrasound format for tissue characterization can be extrapolated for a similar analysis of PA signals.…”
Section: Introductionmentioning
confidence: 99%